High-density multielectrode arrays bring cellular resolution to neuronal activity and network analyses of corticospinal motor neurons - Christopher A. Quintanilla; Zachary Fitzgerald; Omar Kashow; Mihailo S. Radojicic; Emel Ulupinar; Dila Bitlis; Baris Genc; Pavle Andjus; Wim van Drongelen; P. Hande Ozdinler (Scientific Reports)
Abstract Corticospinal motor neurons (CSMN), located in the motor cortex of the brain, are one of the key components of the motor neuron circuitry. They are in part responsible for the initiation and modulation of voluntary movement, and their degeneration is the hallmark for numerous diseases, such as amyotrophic lateral sclerosis (ALS), hereditary spastic paraplegia, and primary lateral sclerosis. Cortical hyperexcitation followed by in-excitability suggests the early involvement of cortical dysfunction in ALS pathology. However, a high-spatiotemporal resolution on our understanding of their functional health and connectivity is lacking. Here, we combine optical imaging with high-density microelectrode array (HD-MEA) system enabling single cell resolution and utilize UCHL1-eGFP mice to bring cell-type specificity to our understanding of the electrophysiological features of healthy CSMN, as they mature and form network connections with other cortical neurons, in vitro. This novel approach lays the foundation for future cell-type specific analyses of CSMN that are diseased due to different underlying causes with cellular precision, and it will allow the assessment of their functional response to compound treatment, especially for drug discovery efforts in upper motor neuron diseases.